2012
DOI: 10.1128/jb.01530-12
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of PhoP/PhoQ and Positive Regulation of the Cyclic AMP Receptor Protein-Cyclic AMP Complex by PhoP in Yersinia pestis

Abstract: Yersinia pestis is one of the most dangerous bacterial pathogens. PhoP and cyclic AMP receptor protein (CRP) are global regulators of Y. pestis, and they control two distinct regulons that contain multiple virulence-related genes. The PhoP regulator and its cognate sensor PhoQ constitute a two-component regulatory system. The regulatory activity of CRP is triggered only by binding to its cofactor cAMP, which is synthesized from ATP by adenylyl cyclase (encoded by cyaA). However, the association between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 38 publications
2
45
0
1
Order By: Relevance
“…In addition, Zhang et al recently showed that the two-component response regulator PhoP directly activates the transcription of both crp and cyaA (33). Thus, considering the distinct environments that Y. pestis inhabits compared to E. coli or even other bacterial pathogens, these data suggest the possibility that divergent mechanisms of crp regulation have evolved that are specific or unique to Yersinia species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhang et al recently showed that the two-component response regulator PhoP directly activates the transcription of both crp and cyaA (33). Thus, considering the distinct environments that Y. pestis inhabits compared to E. coli or even other bacterial pathogens, these data suggest the possibility that divergent mechanisms of crp regulation have evolved that are specific or unique to Yersinia species.…”
Section: Discussionmentioning
confidence: 99%
“…28 Moreover, Y. pestis PhoP was shown to activate crp expression in rich medium. 29 However, in contrast to Y. pestis, PhoP does not affect crp expression and Crp levels in Y. pseudotuberculosis when cultured in rich medium. The species-specific differences are surprising, since the crp, csrB, csrC, and the rovA promoter regions are highly conserved between Y. pestis and Y. pseudotuberculosis, 55,56 indicating that different regulator variants or other regulatory elements participate in the control of the Csr system in different yersiniae.…”
Section: Discussionmentioning
confidence: 94%
“…1). 28,29 In order to test the role of PhoP in Y. pseudotuberculosis, we first investigated the influence of the response regulator on RovA expression in the wild-type strains YPIII and IP32953. Both strains have most frequently been used to elucidate Y. pseudotuberculosis pathogenicity.…”
Section: Phop Activates Rova Expression In Y Pseudotuberculosis Via mentioning
confidence: 99%
See 1 more Smart Citation
“…Other proteins can regulate expression of the crp gene, suggesting that multiple input signals modulate expression of the Crp regulon. The two-component system PhoPQ and the small RNA chaperone Hfq regulate crp in Y. pestis (6,20,21). In turn, Crp regulates expression of the type III secretion system and the Pla protease essential for pneumonic plague (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%